(untitled) (Conferencea, 2023)
This article discusses the legal status of the object and subjects of distance education, understanding the right to education as a standard of freedom, the essence of the object of organizational and legal foundations of distance education, understanding the issue of the subject of distance education, the main participants of distance education, the legal status of the educational institution.